2005
DOI: 10.1261/rna.7287505
|View full text |Cite
|
Sign up to set email alerts
|

Co-evolution of tRNA 3′ trailer sequences with 3′ processing enzymes in bacteria

Abstract: Maturation of the tRNA 3 terminus is a complicated process in bacteria. Usually, it is initiated by an endonucleolytic cleavage carried out by RNase E and Z in different bacteria. In Escherichia coli, RNase E cleaves AU-rich sequences downstream of tRNA, producing processing intermediates with a few extra residues at the 3 end; these are then removed by exoribonuclease trimming to generate the mature 3 end. Here we show that essentially all E. coli tRNA precursors contain a potential RNase E cleavage site, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 48 publications
2
26
0
Order By: Relevance
“…Homologs of RNase E exist in most bacteria, some archaea, as well as in some algae and higher plants ( Lee and Cohen 2003;Li et al 2005;Bollenbach et al 2007;Horie et al 2007). Several Gram-negative bacteria contain two proteins of this family, for example, RNase E and RNase G in E. coli, while others such as cyanobacteria contain only one (Kaberdin et al 1998;Lee and Cohen 2003).…”
Section: Conservation Of Rnase E In Prokaryotes and Photosynthetic Ormentioning
confidence: 99%
“…Homologs of RNase E exist in most bacteria, some archaea, as well as in some algae and higher plants ( Lee and Cohen 2003;Li et al 2005;Bollenbach et al 2007;Horie et al 2007). Several Gram-negative bacteria contain two proteins of this family, for example, RNase E and RNase G in E. coli, while others such as cyanobacteria contain only one (Kaberdin et al 1998;Lee and Cohen 2003).…”
Section: Conservation Of Rnase E In Prokaryotes and Photosynthetic Ormentioning
confidence: 99%
“…RNase R is more widespread in eubacteria than is RNase II (Zuo and Deutscher 2001;Li et al 2005). Interestingly, only one putative exoribonuclease has been identified in Mycoplasma genitalium based on extensive sequence analysis.…”
Section: Introductionmentioning
confidence: 99%
“…All conserved regions of EcR are present in MgR. Based on exhaustive data mining, including PHI-BLAST, multiple sequence alignment and motif identification, no other exoribonuclease is identifiable in Mycoplasma (Zuo and Deutscher 2001;Li et al 2005). Although it is possible that other exoribonuclease(s) may exist without significant sequence similarity to previously characterized nucleases, it is clear that homologs of most exoribonucleases are not encoded in the small genomes of Mycoplasma, and that RNase R likely functions in multiple aspects of RNA metabolism in this organism.…”
Section: Introductionmentioning
confidence: 99%
“…It is unknown how this organism carries out RNA metabolism, a process usually requiring the action of numerous RNases in other bacteria. Surprisingly, none of the RNases listed above for tRNA 3Ј-maturation was identified in M. genitalium and related species (2,9,10). Recently, we demonstrated that purified RNase R of M. genitalium exhibits 3Ј 3 5Ј exoribonuclease activity that is somewhat different from the activities of its E. coli homologues RNases R and II (11).…”
mentioning
confidence: 89%
“…The 5Ј-leader sequences in tRNA precursors are removed ubiquitously by RNase P. At the 3Ј-end, the extra sequences are removed by a variety of different mechanisms. In bacteria, tRNA 3Ј-processing may be accomplished by the actions of endo-or exoribonucleases or both (1,2). In Escherichia coli, the primary tRNA transcript undergoes an initial cleavage by RNase E in its 3Ј-trailer downstream of the CCA sequence (3,4), followed by stepwise trimming reactions of the extra residues by multiple exoribonucleases, including RNases T, PH, D, II, and BN and polynucleotide phosphorylase (5,6).…”
mentioning
confidence: 99%